Residents' Awareness of Forestry Knowledge and Practices for Flood Mitigation (A Case in South West Nigeria) - Adebayo Samson Adeoye; Olawale Julius Aluko; Oluwole Olalekan Oke (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
The combination of environmental degradation and inadequate engineering solutions has exacerbated flooding in Nigeria. Consequently, the study examined residents' awareness of forestry knowledge and practices. A 4-stage random sampling procedure was used, resulting in 250 participants selected via systematic sampling. Data were gathered through a structured questionnaire on residents' demographic characteristics, awareness of environmental practices, and utilization of forestry land-use practices. The analysis of data involved frequencies, percentages, mean values, rankings, and inferential statistics using the Chi-square test. The results showed that 68.0% of respondents were female, with a significant proportion (78.0%) aged 21-50 years. Additionally, 74.0% were married, 40.0% were civil servants, and 22.0% were involved in trading. The residents' knowledge revealed that the prohibition on disposing of refuse into drainage and rivers had a mean score of 1.6 and ranked 1st, while the government's advisories on relocation from flood-prone areas had a mean of 1.1, ranking 2nd in awareness. Chi-square analysis showed significant relationships between tree planting and flood experiences (χ² = 8.18, p = 4×10^-3) and between tree conservation and marital status (χ² = 10.61, p = 0.01). Furthermore, there was a significant association between other demographics, such as marital status (χ²=7.99, p = 0.05) and years of residence (χ²=16.03, p = 3˟10ˉ³), and forestry land use practices (FLUP). Key findings emphasized the critical role of tree planting, conservation, and environmental education in enhancing ecosystem resilience and mitigating climate-related disasters, such as floods, in southwest Nigeria.